The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/s2665-9913(20)30277-0
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab among patients with COVID-19 in the intensive care unit: a multicentre observational study

Abstract: Background Tocilizumab, a monoclonal antibody directed against the interleukin-6 receptor, has been proposed to mitigate the cytokine storm syndrome associated with severe COVID-19. We aimed to investigate the association between tocilizumab exposure and hospital-related mortality among patients requiring intensive care unit (ICU) support for COVID-19. Methods We did a retrospective observational cohort study at 13 hospitals within the Hackensack Meridian Health network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
229
3
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(267 citation statements)
references
References 27 publications
(40 reference statements)
20
229
3
7
Order By: Relevance
“…Indeed, the role of dexamethasone is endorsed by the recent positive report from the RECOVERY trial that showed a significant survival benefit at 28-days among patients who required either invasive mechanical ventilation or oxygen alone at randomization but not among those receiving no respiratory support [27]. Furthermore, there is emerging evidence of the importance of pro-inflammatory cytokines interleukin-6 (IL-6) and tumour necrosis factor (TNF-alpha) as predictors of mortality in patients with COVID-19 [28] and that IL-6 blockade appears to be beneficial [29]. Biran et alhave recently reported in a retrospective multi-centre observational study of 764 patients with severe SARS-CoV-2 infection requiring ICU support that treatment with a recombinant monoclonal antibody against the interleukin (IL)-6 receptor, Tocilizumab ® , was associated with a 25% reduction in hospital-related mortality [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the role of dexamethasone is endorsed by the recent positive report from the RECOVERY trial that showed a significant survival benefit at 28-days among patients who required either invasive mechanical ventilation or oxygen alone at randomization but not among those receiving no respiratory support [27]. Furthermore, there is emerging evidence of the importance of pro-inflammatory cytokines interleukin-6 (IL-6) and tumour necrosis factor (TNF-alpha) as predictors of mortality in patients with COVID-19 [28] and that IL-6 blockade appears to be beneficial [29]. Biran et alhave recently reported in a retrospective multi-centre observational study of 764 patients with severe SARS-CoV-2 infection requiring ICU support that treatment with a recombinant monoclonal antibody against the interleukin (IL)-6 receptor, Tocilizumab ® , was associated with a 25% reduction in hospital-related mortality [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is emerging evidence of the importance of pro-inflammatory cytokines interleukin-6 (IL-6) and tumour necrosis factor (TNF-alpha) as predictors of mortality in patients with COVID-19 [28] and that IL-6 blockade appears to be beneficial [29]. Biran et alhave recently reported in a retrospective multi-centre observational study of 764 patients with severe SARS-CoV-2 infection requiring ICU support that treatment with a recombinant monoclonal antibody against the interleukin (IL)-6 receptor, Tocilizumab ® , was associated with a 25% reduction in hospital-related mortality [29]. Randomised trials are required to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the period prior to the induction of acquired immunity might be a key decisive point for the clinical outcome of severe cases in which the control of viral replication without hyperin ammation is needed. Along the same line, it has been shown that the anti-in ammatory drugs dexamethasone and anti-IL-6 receptor monoclonal antibody reduce the mortality rate of severe COVID-19 cases [35][36][37][38] . We speculate that the emergence of the PMN-MDSC subset prolongs survival by suppressing excessive in ammation until acquired immunity is introduced.…”
Section: Discussionmentioning
confidence: 90%
“…Baricitinib Inflammatory diseases, rheumatoid Arthritis 90,91 Reducing inflammatory responses, 90,91 having a greater efficiency in combination with RDV and LPV-RTV, 93 having the possibility of creating anemia 95,96 Corticosteroids (CSs) Inflammatory diseases 98 Reducing mortality, 102 having short-term or long-term side effects Anakinra Inflammatory diseases 108 Having good performance, reducing mortality, [110][111][112] Tocilizumab (TCZ) Inflammatory diseases, rheumatoid arthritis 116 Showing significant clinical progress, reducing inflammatory markers, reducing mortality, reducing the risk of invasive mechanical ventilation, improving oxygen delivery in patients, having few side effects [117][118][119][120][121][122][123] Anticoagulants Heparin Coagulation problems 130 Reducing mortality, 129 having side effects including drug resistance and heparin-induced thrombocytopenia (HIT) 130,131 Nafamostat mesylate Coagulation problems 134 Having the ability for in vitro inhibition of SARS-CoV-2 S protein-mediated cell fusion and its infection, [132][133][134] improving clinical conditions in patients in need of supplementary oxygen therapy. 135 Arbidol (ARB)…”
Section: Immune Modulatorsmentioning
confidence: 99%
“…116 It has been reported that TCZ reduces mortality in patients with severe COVID-19. 117 A study was conducted in Italy on 100 patients with COVID-19 and ARDS to evaluate the effect of TCZ.…”
Section: Tocilizumab (Tcz)mentioning
confidence: 99%